Profiling of Human Molecular Pathways Affected by Retrotransposons at the Level of Regulation by Transcription Factor Proteins - Nikitin, Daniil; Penzar, Dmitry; Garazha, Andrew; Sorokin, Maxim; Tkachev, Victor; Borisov, Nicolas; Poltorak, Alexander; Prassolov, Vladimir; Buzdin, Anton A. (Frontiers in Immunology, 2018)
Endogenous retroviruses and retrotransposons also termed retroelements (REs) are mobile genetic elements that were active until recently in human genome evolution. REs regulate gene expression by actively reshaping chromatin structure or by directly providing transcription factor binding sites (TFBS). We aimed to identify molecular processes most deeply impacted by the REs in human cells at the level of TFBS regulation. Using ENCODE data, we identified ~2 million TFBS overlapping with putatively regulation-competent human REs located in 5kb gene promoter neighborhood (~17% of all TFBS in promoter neighborhoods; ~9% of all RE-linked TFBS). Most of REs hosting TFBS were highly diverged repeats, and for the evolutionary young (0-8% diverged) elements we identified only ~7% of all RE-linked TFBS. The gene-specific distributions of RE-linked TFBS generally correlated with the distributions for all TFBS. However, several groups of molecular processes were highly enriched in the RE-linked TFBS regulation. They were strongly connected with the immunity and response to pathogens, with the negative regulation of gene transcription, ubiquitination and protein degradation, extracellular matrix organization, regulation of STAT signaling, fatty acids metabolism, regulation of GTPase activity, protein targeting to Golgi, regulation of cell division and differentiation, development and functioning of perception organs and reproductive system. In contrast, the processes most weakly affected by the REs were linked with the conservative aspects of embryo development. We also identified differences in the regulation features by the younger and older fractions of the REs. The regulation by the older fraction of the REs was linked mainly with the immunity, cell adhesion, cAMP, IGF1R, Notch, Wnt and integrin signaling, neuronal development, chondroitin sulfate and heparin metabolism and endocytosis. The younger REs regulate other aspects of immunity, cell cycle progression and apoptosis, PDGF, TGF beta, EGFR and p38 signaling, transcriptional repression, structure of nuclear lumen, catabolism of phospholipids and heterocyclic molecules, insulin and AMPK signaling, retrograde Golgi-ER transport and estrogen signaling. The immunity-linked pathways were highly represented in both categories, but their functional roles were different and did not overlap. Our results point to the most quickly evolving molecular pathways in the recent and ancient evolution of human genome.